The Growth and Development of Winter Wheat in the Conditions of Lead and Oil Pollution - I. Kolesnikov, Sergey; G. Zharkova, Maria; Sh. Kazeev, Kamil; V. Denisova, Tatyana; V. Akimenko, Yuliy (International Journal of Engineering and Technology, 2018)
Exceeding the background lead content in ordinary chernozem by 25 mg/kg, and the oil content of 0.25% of soil weight, cannot be considered environmentally safe. These doses cause significant impairment of growth and development of winter wheat. Moreover, lead enters grain and straw in large amounts.Â Â